Planned incremental development a new approach to provide affordability in socialized housing - Babia, Karen S. (2011)
The urbanization process causes most of the informal settlers and slum dwellers reside in urban centers and its fringe. This trend results in land insecurity and disaster prone housing set-ups. Moreover, low-cost housing organized by the government cannot fully provide housing units for the low-income families due to its high monthly payments and attained user's satisfaction. The researcher had conducted a study which aims to determine the most affordable building materials used in housing. Through participatory process, the desired site planning, house design and the possible materials to be used were established by the respondents of the study and further was consolidated and finalized by the researcher. According to the data collected, the cheapest building materials are the interlocking compressed earth block for the firewalls, and coconut fiber board for the interior and exterior walls. Yet, the total amount of the house is still far beyond the monthly income of the respondents. In addition, the whole construction is divided into different phases. Each phase is determined through its total cost, materials used and the time frame of construction